PICO-based problem solving (question-answer) of the ST-segment elevation in the aVR lead in a patient with chest pain referred to a hospital emergency department: Letter to Editor - Ali MoeziBady; Mohammad Yousof Qoddusi; Nahid Azdaki; Nazanin Hanafi Bojd; Neda Partovi (مجله دانشگاه علوم پزشکی بیرجند, 2022)
In evidence-based medicine, constructing research questions is the most important part of research integration. Formulating a research question is the first step to conducting a credible and valuable research. Patient, intervention, comparison, outcome (PICO) is a specialized framework used by most researchers to formulate a research question and facilitate resource review. In the heart ward of Razi Hospital, Birjand University of Medical Sciences, according to the needs assessments, PICO was implemented during the Journal Club to familiarize students with research and increase their level of knowledge, attitude, as well as clinical reasoning skills. In this article, we explain the case of a 36-year-old woman with typical chest pain for 3 hours due to severe stress, without cardiac risk factors referring to the emergency room. The clinical examination was normal. The ST elevation was observed in the aVR lead. The question is “Should we perform an invasive intervention for this patient?